Numerical investigation of plasma edge transport and limiter heat fluxes in Wendelstein 7-X startup plasmas with EMC3-EIRENE. (20th January 2017) - Effenberg, F.; Feng, Y.; Schmitz, O.; Frerichs, H.; Bozhenkov, S.A.; Hölbe, H.; König, R.; Krychowiak, M.; Pedersen, T. Sunn; Reiter, D.; Stephey, L.
Abstract: The results of a first systematic assessment of plasma edge transport processes for the limiter startup configuration at Wendelstein 7-X are presented. This includes an investigation of transport from intrinsic and externally injected impurities and their impact on the power balance and limiter heat fluxes. The fully 3D coupled plasma fluid and kinetic neutral transport Monte Carlo code EMC3-EIRENE is used. The analysis of the magnetic topology shows that the poloidally and toroidally localized limiters cause a 3D helical scrape-off layer (SOL) consisting of magnetic flux tubes of three different connection lengths L C . The transport in the helical SOL is governed by L C as topological scale length for the parallel plasma loss channel to the limiters. A clear modulation of the plasma pressure with L C is seen. The helical flux tube topology results in counter streaming sonic plasma flows. The heterogeneous SOL plasma structure yields an uneven limiter heat load distribution with localized peaking. Assuming spatially constant anomalous transport coefficients, increasing plasma density yields a reduction of the maximum peak heat loads from 12 MWm −2 to 7.5 MWm −2 and a broadening of the deposited heat fluxes. The impact of impurities on the limiter heat loads is studied by assuming intrinsic carbon impurities eroded from the limiter surfaces with a gross chemical sputtering yield of 2 % . The resulting radiative losses account for less than 10% of the input power in the power balance with marginal impact on the limiter heat loads. It is shown that a significant mitigation of peak heat loads, 40–50%, can be achieved with controlled impurity seeding with nitrogen and neon, which is a method of particular interest for the later island divertor phase.